A microencapsulation approach to design microbial seed coatings to boost wheat seed germination and seedling growth under salt stress - Gong, Min; He, Jiuxing; Kong, Meng; Huo, Qiuyan; Jiang, Yawen; Song, Jiqing; Han, Wei; Lv, Guohua (Frontiers in Plant Science, 2023)
Salt stress in seed germination and early seedling growth is the greatest cause of crop loss in saline-alkali soils. Microbial seed coating is an effective way to promote plant growth and salt resistance, but these coatings suffer from poor seed adhesion and low survival rates under typical storage conditions. In this study, the marine bacterium Pontibacter actiniarum DSM 19842 from kelp was isolated and microencapsulated with calcium alginate using the emulsion and internal gelation method. Compared to unencapsulated seeds, the spherical microcapsules demonstrated a bacterial encapsulation rate of 65.4% and survival rate increased by 22.4% at 25°C for 60 days.Under salt stress conditions, the seed germination percentage of microcapsule-embedded bacteria (M-Embed) was 90%, which was significantly increased by 17% compared to the germination percentage (73%) of no coating treatment (CK). Root growth was also significantly increased by coating with M-Embed. Chlorophyll, peroxidase, superoxide dismutase, catalase, proline, hydrogen peroxide and malondialdehyde levels indicated that the M-Embed had the best positive effects under salt stress conditions. Therefore, embedding microorganisms in suitable capsule materials provides effective protection for the survival of the microorganism and this seed coating can alleviate salt stress in wheat. This process will benefit the development of sustainable agriculture in coastal regions with saline soils.